Analysis of the Distribution of Village Funds (ADD) Allocation Mechanism to the Village Government - Zurroida Nurfatmi; Isnaini Rodiyah (Indonesian Journal of Cultural and Community Development, 2021)
The Village Fund Allocation (ADD) is a balancing fund originating from the Regency/City Government submitted to the Village Government which is expected to be the main buffer for the implementation of community empowerment and village development so as to improve community welfare. The purpose of this study was to determine the mechanism for distributing the Village Fund Allocation (ADD). This research located Wunut Village, District Porong, Sidoarjo Regency. The type of data used is qualitative. The results showed that the Village Fund Allocation (ADD) distribution mechanism in the APBDesa was carried out in stages, namely stages I, II, III, and IV. However, there was a delay in achieving the program planned by the village because the disbursement of the Village Fund Allocation (ADD) was carried out in stages and other factors were due to delays from other villages in providing accountability reports. it has an impact on other villages.